Elite female endurance athletes are at increased risk of atrial fibrillation compared to the general population: a matched cohort study - Drca, N.; Larsson, S. C.; Grannas, D.; Jensen-Urstad, M. (British Journal of Sports Medicine, 2023)
Objective Previous studies have found that endurance sport activity is associated with an increased risk of atrial fibrillation (AF) in men. However, it remains unclear whether endurance sports also influence the risk of AF in women. We aimed to examine whether participation in endurance sports may affect the risk of AF in female athletes.